2003
DOI: 10.1046/j.1365-2036.2003.01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic function testing

Abstract: SUMMARYPancreatic function tests are most commonly used to diagnose chronic pancreatitis. These tests include tests which document exocrine or endocrine gland insufficiency and tests which instead measure gradations of decreased secretory capacity. The tests in the former category generally become abnormal when advanced, longstanding chronic pancreatitis is present. Tests in the latter category, however, have the potential to detect chronic pancreatitis at an earlier stage than other available diagnostic tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(135 citation statements)
references
References 129 publications
4
122
0
9
Order By: Relevance
“…Such tests are sensitive but poorly specific, i.e. they are not diagnostic [105,106]. Conversely, tubeless tests of pancreatic function can detect severe exocrine insufficiency only [107][108][109].…”
Section: C7mentioning
confidence: 99%
“…Such tests are sensitive but poorly specific, i.e. they are not diagnostic [105,106]. Conversely, tubeless tests of pancreatic function can detect severe exocrine insufficiency only [107][108][109].…”
Section: C7mentioning
confidence: 99%
“…The use of invasive function tests (secretin test, pancreozymin-secretin test) is declining over the last years. In recent reviews it was stated that invasive function tests in combination with pancreatic calcification are still the gold standard in the diagnosis of chronic pancreatitis, but these tests are laborious and costly [23][24][25][26]. Non-invasive tests (faecal chymotrypsin, PABA-, pancreolauryl-and faecal elastase test) are insufficient for the detection of minor or moderate insufficiency as a result of their restricted sensitivity compared to the pancreozymin-secretin test.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Based on the underlying cause of pancreatic insufficiency, the levels of these secretions will vary considerably from one individual to another. It also has been reported that patients may be deficient in only some enzymes and not others [24].…”
Section: Physiological Sources Of Variabilitymentioning
confidence: 98%
“…A spot fecal elastase 1 test from a stool sample was used to confirm pancreatic enzyme insufficiency in patients [22]. Subjects were selected for the study only if the spot fecal elastase 1 was <200 µg/g at the time of screening [23][24][25].…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation